Adhesive formulations based on ethylene multi-block interpolymers and functionalized propylene-based polymers

By using ingredients such as ethylene/α-allyl multiblock interpolymer and functionalized propylene-based polymer in hot melt adhesives, combined with tackifier and wax, the problem of hot melt adhesives in the prior art is difficult to achieve high thermal stability and rapid curing at the same time, achieving fiber tear strength of more than 90% and curing within 2.0 seconds.

JP7662763B2Active Publication Date: 2025-04-15DOW GLOBAL TECHNOLOGIES LLC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023505848
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-29
Publication Date
2025-04-15
Estimated Expiration
2040-07-29

AI Technical Summary

Technical Problem

Existing hot melt adhesives are difficult to achieve high thermal stability and fast curing time in packaging applications, and cannot meet the needs of certain cartoon and box packaging applications.

Method used

Using a combination of hot melt adhesive composed of ethylene/α-allyl multiblock interpolymer, functionalized propylene-based polymer, tackifier and wax, the balance of high thermal stability and rapid curing is achieved by optimizing the proportion and performance of these ingredients.

Benefits of technology

The fiber tear strength of the adhesive at 70°C is achieved and cured in 2.0 seconds, meeting the dual requirements of high thermal stability and rapid curing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662763000001
    Figure 0007662763000001
  • Figure 0007662763000002
    Figure 0007662763000002
  • Figure 0007662763000003
    Figure 0007662763000003
Patent Text Reader

Abstract

A hot melt adhesive (HMA) composition includes: a) an ethylene / alpha-olefin multi-block interpolymer having a melt viscosity at 177°C of ≦50,000 mPa·s; b) an anhydride- and / or carboxylic acid-functionalized propylene-based polymer having a melt viscosity at 190°C of ≦50,000 mPa·s; c) a tackifier; and d) a wax. Such a composition provides both high temperature resistance and fast cure times.
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] Hot melt adhesives (HMA) used in packaging applications are typically formulated with low viscosity polymers, tackifiers, and waxes to form a final composition with a predetermined performance property profile. Typical performance properties of packaging HMAs include viscosity at application temperature, some measure of heat resistance of the bond (e.g., PAFT and SAFT), open and set times, and usually an indication of adhesion in terms of fiber tear over a temperature range. Some carton and case sealing applications require packaging hot melt adhesives to have both high heat resistance and fast set times, a combination that is currently an unmet need in the market. Therefore, there is a need for adhesive formulations that provide both high temperature heat resistance (e.g., ≧90% fiber tear (at 70° C.)) and short set times (e.g., ≦2.0 seconds).

[0002] U.S. Patent Application Publication No. 2018 / 0244962 discloses a method for producing a cellulose ester copolymer comprising: (a) about 5% to about 50% by weight of a functionalized polymer comprising a metallocene-catalyzed random polyolefin elastomer grafted with maleic anhydride; (b) about 5% to about 70% by weight of a non-functionalized polymer comprising a metallocene-catalyzed random or block polyolefin elastomer having a melt index of 15 or greater as a second polymer; and (c) up to about 30% by weight of a non-functionalized polymer comprising a metallocene-catalyzed random or block polyolefin elastomer having a melt index of 15 or greater as a second polymer. (d) about 5% to about 30% by weight of a wax; (e) about 20% to about 70% by weight of a first tackifying resin having a softening point of at least about 95°C; (f) about 0% to about 20% by weight of an aromatic toughening resin having a softening point of 115°C or higher; (g) about 0.1% to about 5% by weight of a stabilizer; and (h) about 0% to about 3% by weight of an auxiliary additive. See claim 1. An example of component (a) is AFFINITY GA 1000R from Dow Chemical Company (see paragraph

[0029] ). The composition may contain an olefin block copolymer (see Tables 1A-1C and Table 2).

[0003] US Patent Application Publication No. 2016 / 0304756 discloses a hot melt adhesive composition comprising (a) an ethylene / alpha-olefin multiblock copolymer having a weight average molecular weight (Mw) of less than 20,000, (b) a tackifier having a softening temperature of 90°C to 150°C, and (c) a wax (see Abstract). The composition may optionally include one or more other polymeric components, such as, for example, a propylene-based polymer and an ethylene-based polymer (functionalized or non-functionalized). See paragraph

[0067] . The wax may be a maleic anhydride modified wax, such as EPOLENE C-18, AC-575A, and AC-575P (see paragraph

[0054] ).

[0004] US Patent Application Publication No. 2012 / 0165455 discloses a hot melt adhesive composition comprising: (a) about 20-70 weight percent of a polyolefin polymer having a melt index (I2) of greater than about 5 g / 10 min; (b) about 2-50 weight percent of an olefin block copolymer (OBC) having a density of about 0.86 g / cc to about 0.89 g / cc; (c) about 10-60 weight percent of a tackifier resin having a softening point of about 95°C to about 140°C; and (d) about 0.1 to about 5 weight percent of an antioxidant. The adhesive composition has a Brookfield viscosity of about 50,000 cP or less at 177°C. See claim 1. EPOLENE C-16 and C-18, each of which is a polyethylene modified with maleic anhydride, may be used in the formulation with the OBC (see paragraph

[0032] ).

[0005] US Patent Application Publication No. 2015 / 0065638 discloses an adhesive composition comprising: a) an olefin block copolymer comprising ethylene and an alpha-olefin comonomer; (b) a tackifier; and (c) an oil. The olefin block copolymer comprises: i) a hard block comprising 1-8 mol % comonomer, the hard block being present in an amount of 20 wt %-45 wt % based on the weight of the olefin block copolymer; and ii) a soft block comprising 10-14 mol % comonomer, the olefin block copolymer having a Mw of 15,000 g / mol-100,000 g / mol, a total crystallinity of 5 wt %-30 wt %, a Tm of 60° C.-115° C., and a Tc of 45° C.-100° C. See claim 1. The composition may include an additional polyolefin, such as a homogeneously branched ethylene / alpha-olefin copolymer or other olefin block copolymer (see paragraphs

[0041] to

[0043] ).

[0006] US Patent No. 10,138,398 discloses a hot melt adhesive composition comprising: (a) about 5% to about 25% by weight of an olefin block copolymer having an average melt index (I2) of more than 5 g / 10 min and less than about 35 g / 10 min at 190° C.; (b) about 40% to about 70% by weight of a tackifier; (c) about 0.5% to about 5% by weight of a wax; (d) about 1% to about 30% by weight of a plasticizer diluent; and (e) 0 to about 5% by weight of optional ingredients such as antioxidants, fillers, pigments, flow control agents, dyes, or mixtures thereof. See claims 1 and 6. The adhesive is disclosed to be useful in the construction of nonwoven articles (see Abstract).

[0007] However, as discussed above, there remains a need for adhesive formulations that provide both high temperature resistance and fast cure times. This need has been met by the following invention. Summary of the Invention

[0008] Ingredients include: a) an ethylene / alpha-olefin multi-block interpolymer having a melt viscosity (177°C) of ≦50,000 mPa·s; b) an anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer having a melt viscosity (190°C) of ≦50,000 mPa·s; c) a tackifier; and d) a wax. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Compositions have been discovered that provide both high temperature resistance and short cure times (e.g., fiber tear (at 70° C.) ≧90% and cure time ≦2.0 seconds). As discussed above, the following components are included: a) an ethylene / alpha-olefin multi-block interpolymer having a melt viscosity (177°C) of ≦50,000 mPa·s; b) an anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer having a melt viscosity (190°C) of ≦50,000 mPa·s; c) a tackifier; and d) a wax.

[0010] The composition may comprise a combination of two or more embodiments as described herein. Each component a)-d) may independently comprise a combination of two or more embodiments as described herein.

[0011] In one embodiment, or a combination of two or more embodiments, each described herein, the ethylene / alpha-olefin multi-block interpolymer (component a) has a melt viscosity (177° C.) of ≦45,000 mPa·s, or ≦40,000 mPa·s, or ≦35,000 mPa·s, or ≦30,000 mPa·s, or ≦28,000 mPa·s, or ≦26,000 mPa·s, or ≦24,000 mPa·s, or ≦22,000 mPa·s, or ≦20,000 mPa·s. In one embodiment, or a combination of two or more embodiments, each described herein, component a has a melt viscosity (177°C) of ≥ 1,000 mPa·s, or ≥ 2,000 mPa·s, or ≥ 3,000 mPa·s, or ≥ 4,000 mPa·s, or ≥ 5,000 mPa·s, or ≥ 6,000 mPa·s, or ≥ 8,000 mPa·s, or ≥ 10,000 mPa·s, or ≥ 12,000 mPa·s, or ≥ 14,000 mPa·s.

[0012] In one embodiment, or a combination of two or more embodiments, each described herein, the ethylene / alpha-olefin multi-block interpolymer (component a) is an ethylene / alpha-olefin multi-block copolymer.

[0013] In one embodiment, or a combination of two or more embodiments, each described herein, the anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer (component b) has a melt viscosity (190° C.) of ≦45,000 mPa·s, or ≦40,000 mPa·s, or ≦35,000 mPa·s, or ≦30,000 mPa·s, or ≦28,000 mPa·s, or ≦26,000 mPa·s, or ≦24,000 mPa·s, or ≦22,000 mPa·s, or ≦20,000 mPa·s, or ≦18,000 mPa·s, or ≦16,000 mPa·s. In one embodiment, or a combination of two or more embodiments, each described herein, component b has a melt viscosity (190° C.) of ≧1,000 mPa·s, or ≧2,000 mPa·s, or ≧3,000 mPa·s, or ≧4,000 mPa·s, or ≧6,000 mPa·s, or ≧8,000 mPa·s, or ≧10,000 mPa·s, or ≧12,000 mPa·s, or ≧14,000 mPa·s.

[0014] In one embodiment, or a combination of two or more embodiments, each described herein, the ethylene / alpha-olefin multi-block interpolymer (component a) has a viscosity of ≥ 0.860 g / cc, or ≥ 0.862 g / cc, or ≥ 0.864 g / cc, or ≥ 0.866 g / cc, or ≥ 0.868 g / cc, or ≥ 0.870 g / cc, or ≥ 0.872 g / cc (1 cc = 1 cm 3 In one embodiment, or a combination of two or more embodiments, each described herein, component a has a density of ≦0.890 g / cc, or ≦0.888 g / cc, or ≦0.886 g / cc, or ≦0.884 g / cc, or ≦0.882 g / cc, or ≦0.880 g / cc, or ≦0.878 g / cc.

[0015] In one embodiment or a combination of two or more embodiments, each of which is described herein, the anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer (component b) has a density of ≧0.888 g / cc, or ≧0.890 g / cc, or ≧0.892 g / cc, or ≧0.894 g / cc, or ≧0.896 g / cc, or ≧0.898 g / cc, or ≧0.900 g / cc, or ≧0.902 g / cc. In one embodiment or a combination of two or more embodiments, each of which is described herein, component b has a density of ≦0.920 g / cc, or ≦0.918 g / cc, or ≦0.916 g / cc, or ≦0.914 g / cc, or ≦0.912 g / cc, or ≦0.910 g / cc, or ≦0.908 g / cc, or ≦0.906 g / cc.

[0016] In one embodiment or a combination of two or more embodiments, each described herein, the anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer (component b) has a melting point (Tm) of ≥ 100°C, or ≥ 105°C, or ≥ 110°C, or ≥ 115°C, or ≥ 120°C, or ≥ 122°C, or ≥ 124°C, or ≥ 126°C, or ≥ 128°C, or ≥ 130°C, or ≥ 131°C. In one embodiment or a combination of two or more embodiments, each described herein, component b has a melting point (Tm) of ≤ 160°C, or ≤ 155°C, or ≤ 150°C, or ≤ 148°C, or ≤ 146°C, or ≤ 144°C, or ≤ 142°C, or ≤ 140°C, or ≤ 138°C, or ≤ 136°C.

[0017] In one embodiment, or a combination of two or more embodiments, each described herein, component b is a grafted propylene anhydride and / or carboxylate based polymer.

[0018] In one embodiment, or a combination of two or more embodiments, each described herein, component b is an anhydride- and / or carboxylic acid-functionalized propylene / ethylene copolymer, and further is a grafted anhydride and / or carboxylic acid propylene / ethylene copolymer.

[0019] In one embodiment, or a combination of two or more embodiments, each described herein, the weight ratio of component a to component b is ≧0.10, or ≧0.15, or ≧0.20, or ≧0.22, or ≧0.24, or ≧0.26, or ≧0.28, or ≧0.30, or ≧0.32. In one embodiment, or a combination of two or more embodiments, each described herein, the weight ratio of component a to component b is ≦5.00, or ≦4.50, or ≦4.00, or ≦3.80, or ≦3.60, or ≦3.40, or ≦3.20, or ≦3.00.

[0020] In one embodiment, or a combination of two or more embodiments, each described herein, the weight ratio of component c to component a is ≧1.00, or ≧1.05, or ≧1.10, or ≧1.15, or ≧1.20, or ≧1.25, or ≧1.30. In one embodiment, or a combination of two or more embodiments, each described herein, the weight ratio of component c to component a is ≦5.00, or ≦4.80, or ≦4.60, or ≦4.40, or ≦4.20, or ≦4.00.

[0021] In one embodiment, or a combination of two or more embodiments, each described herein, the weight ratio of component c to component b is ≧1.00, or ≧1.05, or ≧1.10, or ≧1.15, or ≧1.20, or ≧1.25, or ≧1.30. In one embodiment, or a combination of two or more embodiments, each described herein, the weight ratio of component c to component b is ≦5.00, or ≦4.80, or ≦4.60, or ≦4.40, or ≦4.20, or ≦4.00.

[0022] In one embodiment, or a combination of two or more embodiments, each described herein, component c is a hydrocarbon resin, or even a hydrogenated hydrocarbon resin, or even a hydrogenated alicyclic hydrocarbon resin.

[0023] In one embodiment, or a combination of two or more embodiments, each described herein, the wax (component d) has a density of ≧0.920 g / cc, or ≧0.925 g / cc, or ≧0.930 g / cc, or ≧0.932 g / cc, or ≧0.934 g / cc, or ≧0.936 g / cc, or ≧0.938 g / cc, or ≧0.939 g / cc, or ≧0.940 g / cc. In one embodiment, or a combination of two or more embodiments, each described herein, component d has a density of ≦0.960 g / cc, or 0≦0.958 g / cc, or ≦0.956 g / cc, or ≦0.954 g / cc, or ≦0.952 g / cc, ≦0.950 g / cc.

[0024] In one embodiment, or a combination of two or more embodiments, each described herein, the wax (component d) has a melt viscosity (135° C.) of ≧4.0 mPa·s, or ≧4.5 mPa·s, or ≧5.0 mPa·s, or ≧5.5 mPa·s, or ≧6.0 mPa·s. In one embodiment, or a combination of two or more embodiments, each described herein, component d has a melt viscosity (135° C.) of ≦30 mPa·s, or ≦25 mPa·s, or ≦20 mPa·s, or ≦18 mPa·s, or ≦16 mPa·s, or ≦14 mPa·s, or ≦12 mPa·s, or ≦10 mPa·s.

[0025] In one embodiment, or a combination of two or more embodiments, each described herein, the composition comprises ≧30.0 wt.%, or ≧32.0 wt.%, or ≧34.0 wt.%, or ≧36.0 wt.%, or ≧38.0 wt.% of the sum of components a and b, based on the weight of the composition. In one embodiment, or a combination of two or more embodiments, each described herein, the composition comprises ≦50.0 wt.%, or ≦48.0 wt.%, or ≦46.0 wt.%, or ≦44.0 wt.%, or ≦42.0 wt.% of the sum of components a and b, based on the weight of the composition.

[0026] In one embodiment, or a combination of two or more embodiments, each described herein, the composition has a melt viscosity (177°C) of ≦8,000 mPa·s, or ≦7,000 mPa·s, or ≦6,000 mPa·s, or ≦5,000 mPa·s, or ≦4,000 mPa·s, or ≦3,000 mPa·s, or ≦2,000 mPa·s. In one embodiment, or a combination of two or more embodiments, each described herein, the composition has a melt viscosity (177° C.) of ≧200 mPa·s, or ≧300 mPa·s, or ≧400 mPa·s, or ≧500 mPa·s, or ≧600 mPa·s, or ≧700 mPa·s, or ≧800 mPa·s, or ≧900 mPa·s, or ≧1,000 mPa·s, or ≧1,100 mPa·s, or ≧1,200 mPa·s, or ≧1,300 mPa·s.

[0027] In one embodiment, or a combination of two or more embodiments, each described herein, the composition has a cure time of ≦2.0 seconds, or ≦1.5 seconds, or ≦1.0 seconds.

[0028] In one embodiment, or a combination of two or more embodiments, each described herein, the composition has a fiber tear (at 70° C.) of ≧90%, or ≧91%, or ≧92%, or ≧93%, or ≧94%.

[0029] Also provided are articles that include at least one component formed from the composition of any one embodiment, or combination of two or more embodiments, each described herein.

[0030] Ethylene / Alpha-Olefin Multiblock Interpolymer Ethylene / alpha-olefin multi-block interpolymers are characterized by multiple blocks or segments of two or more polymerized monomer units that differ in chemical or physical properties. In some embodiments, the multi-block copolymers have the following formula: (AB): nwhere n is at least 1 and preferably an integer greater than 1, for example, 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100 or more. "A" represents a hard block or segment, and "B" represents a soft block or segment. Preferably, the A and B segments are linked in a substantially linear fashion, as opposed to a substantially branched or substantially star-shaped fashion. In other embodiments, the A and B segments are randomly distributed along the polymer chain. In other words, for example, a block copolymer does not usually have the following structure: AAA-AA-BBB-BB. In still other embodiments, a block copolymer does not usually have a third type of block or segment that includes a different comonomer. In still other embodiments, each of the blocks A and B has a monomer or comonomer that is substantially randomly distributed within the block. In other words, neither block A nor block B includes two or more sub-segments (or sub-blocks) of distinct composition, such as a tip segment having a substantially different composition than the remainder of the block.

[0031] As used herein, the term "hard segment (HS)" refers to a block of polymerized monomer units in which ethylene is present in an amount of >90 mol%, or ≧92 mol%, or ≧95 mol%, or ≧98 mol%, or ≧99 mol%, based on the total moles of polymerized monomers in the block. In one embodiment, ethylene is present in an amount of ≦99.8 mol%, or ≦99.6 mol%, or ≦99.4 mol%, or ≦99.3 mol%, based on the total moles of polymerized monomers in the block.

[0032] As used herein, the term "soft segment (SS)" refers to a block of polymerized monomer units in which ethylene is present in an amount of ≦90 mol%, or ≦88 mol%, or ≦86 mol%, or ≦84 mol%, based on the total moles of polymerized monomers in the block. In one embodiment, ethylene is present in an amount of ≧80 mol%, or ≧81 mol%, or ≧82 mol%, based on the total moles of polymerized monomers in the block.

[0033] Typically, ethylene comprises 50 or the majority of the mole percent of the total multi-block copolymer. That is, ethylene comprises at least 50 mole percent of the whole polymer. More preferably, ethylene comprises at least 60 mole percent, at least 70 mole percent, or at least 80 mole percent, with the substantial remainder of the whole polymer being at least one other comonomer, which is preferably an alpha-olefin having 3 or more carbon atoms.

[0034] As discussed, ethylene / alpha-olefin multi-block interpolymers preferably contain two or more chemically distinct regions or segments (referred to as "blocks") that are linearly linked. In one embodiment, the blocks differ in the amount or type of incorporated comonomer, density, amount of crystallinity, crystallite size resulting from polymers of such composition, type or degree of stereoregularity (isotactic or syndiotactic), regioregularity or site irregularity, amount of branching (including long chain branching or hyperbranching), uniformity, or any other chemical or physical property. Compared to prior art block interpolymers, including interpolymers produced by continuous monomer addition, flow catalyst, or anionic polymerization techniques, the ethylene / alpha-olefin multi-block interpolymers of the present invention are, in one embodiment, characterized by a unique distribution of both polymer polydispersity (PDI or Mw / Mn or MWD), block length distribution, and / or block number distribution due to the effect of shuttling agents in combination with the multiple catalysts used in their preparation.

[0035] Olefin block copolymers are generally produced via a chain shuttling process, such as that described in U.S. Pat. No. 7,858,706, which is incorporated herein by reference. Some chain shuttling agents and related information are listed in column 16, line 39 to column 19, line 44. Some catalysts are listed in column 19, line 45 to column 46, line 19, and some cocatalysts are listed in column 46, line 20 to column 51, line 28. Some process features are listed in column 51, line 29 to column 54, line 56. See also: U.S. Pat. Nos. 7,608,668, 7,893,166, and 7,947,793, and U.S. Patent Publication No. 2010 / 0197880. See also U.S. Pat. No. 9,243,173.

[0036] Tackifier Tackifiers are known in the art and can be solid, semi-solid, or liquid at room temperature. Tackifiers include, but are not limited to, aliphatic, cycloaliphatic, and aromatic hydrocarbons, modified hydrocarbons, and hydrogenated versions of such hydrocarbons, terpenes, modified terpenes, and hydrogenated versions of such terpenes, as well as rosins, rosin derivatives, and hydrogenated versions of such rosins, and mixtures of two or more of these tackifiers.

[0037] wax Waxes include, but are not limited to, paraffin waxes, microcrystalline waxes, high density low molecular weight polyethylene or polypropylene waxes, pyrolysis waxes, by-product polyethylene waxes, Fischer-Tropsch waxes, oxidized Fischer-Tropsch waxes, and functionalized waxes, such as hydroxyl stearamide waxes, and fatty amide waxes, as well as mixtures of two or more of these waxes.

[0038] definition Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.

[0039] As used herein, the term "composition" includes mixtures of materials, including compositions and reaction products and decomposition products formed from the materials of the composition. Any reaction or decomposition products are typically present in trace or residual amounts.

[0040] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerizing the same or different types of monomers. Thus, the generic term polymer includes the term homopolymer (used to refer to a polymer prepared from only one type of monomer, with the understanding that trace amounts of impurities may be incorporated into the polymer structure), and the term interpolymer, as defined herein below. Trace amounts of impurities, such as catalyst residues, may be incorporated into and / or within the polymer. Typically, polymers are stabilized with very small amounts ("ppm" amounts) of one or more stabilizers (e.g., antioxidants).

[0041] The term "interpolymer," as used herein, refers to a polymer prepared by the polymerization of at least two different types of monomers. Thus, the term interpolymer includes the term copolymer, which is used to refer to a polymer prepared from two different types of monomers, and polymers prepared from more than two different types of monomers.

[0042] As used herein, the term "olefin-based polymer" refers to a polymer that, in polymerized form, contains 50 weight percent or majority weight percent (based on the weight of the polymer) of an olefin, such as ethylene or propylene, and may optionally contain one or more comonomers.

[0043] As used herein, the term "propylene-based polymer" refers to a polymer that, in polymerized form, contains a majority weight percent propylene (based on the weight of the polymer) and may optionally contain one or more comonomers.

[0044] As used herein, the term "propylene / alpha-olefin interpolymer" refers to a random interpolymer that comprises, in polymerized form, a majority weight percent (based on the weight of the interpolymer) of propylene and an alpha-olefin.

[0045] As used herein, the term "propylene / alpha-olefin copolymer" refers to a random copolymer that, in polymerized form, contains a majority weight percent of propylene (based on the weight of the copolymer) and an alpha-olefin as the only two monomer types.

[0046] As used herein, the term "propylene / ethylene interpolymer" refers to a random interpolymer that comprises, in polymerized form, a majority weight percent of propylene and ethylene (based on the weight of the interpolymer).

[0047] As used herein, the term "propylene / ethylene copolymer" refers to a random copolymer that, in polymerized form, contains a majority weight percent of propylene (based on the weight of the copolymer) and ethylene as the only two monomer types.

[0048] As used herein, the term "ethylene-based polymer" refers to a polymer that, in polymerized form, contains at least 50 weight percent or majority weight percent ethylene (based on the weight of the polymer) and may optionally contain one or more comonomers.

[0049] As used herein, the term "ethylene / alpha-olefin multi-block interpolymer" refers to a multi-block interpolymer that contains, in polymerized form, 50% or a majority weight percent of ethylene (based on the weight of the interpolymer) and an alpha-olefin. As used herein, the term "ethylene / alpha-olefin multi-block copolymer" refers to a multi-block copolymer that contains, in polymerized form, 50% or a majority weight percent of ethylene monomer (based on the weight of the copolymer) and an alpha-olefin as the only two monomer types. See also the discussion above.

[0050] As used herein, the term "ethylene / alpha-olefin interpolymer" refers to a random interpolymer that comprises, in polymerized form, 50 weight percent or a majority weight percent (based on the weight of the interpolymer) of ethylene and an alpha-olefin.

[0051] As used herein, the term "ethylene / alpha-olefin copolymer" refers to a copolymer that, in polymerized form, contains 50 weight percent or majority weight percent ethylene monomer (based on the weight of the copolymer) and an alpha-olefin as the only two monomer types.

[0052] As used herein, the term "anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer" refers to a propylene-based polymer that contains anhydride and / or carboxylic acid groups. Such anhydride and / or carboxylic acid groups may be derived from maleic anhydride or other anhydride compounds. The anhydride groups may be converted to carboxylic acid groups by reaction with water.

[0053] The phrase "major weight percent" as used herein with respect to a polymer (or interpolymer or copolymer) refers to the amount of monomer that is present in the greatest amount in the polymer.

[0054] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not they are specifically disclosed. For the avoidance of doubt, all compositions claimed through the use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless specifically stated to the contrary. In contrast, the term "consisting essentially of" excludes those that are not essential to operability and excludes any other component, step, or procedure from the scope of any subsequent recitation. The term "consisting of" excludes any component, step, or procedure not specifically defined or listed.

[0055] Listing some compositional features A] The following ingredients: a) an ethylene / alpha-olefin multi-block interpolymer having a melt viscosity (177°C) of ≦50,000 mPa·s; b) an anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer having a melt viscosity (190°C) of ≦50,000 mPa·s; c) a tackifier; and d) a wax.

[0056] B] The composition described in A] above, wherein the ethylene / alpha-olefin multi-block interpolymer (component a) has a melt viscosity (177°C) of ≦45,000 mPa·s, or ≦40,000 mPa·s, or ≦35,000 mPa·s, or ≦30,000 mPa·s, or ≦28,000 mPa·s, or ≦26,000 mPa·s, or ≦24,000 mPa·s, or ≦22,000 mPa·s, or ≦20,000 mPa·s.

[0057] C] The composition described in A] or B] above, wherein component a has a melt viscosity (177°C) of ≧1,000 mPa·s, or ≧2,000 mPa·s, or ≧3,000 mPa·s, or ≧4,000 mPa·s, or ≧5,000 mPa·s, or ≧6,000 mPa·s, or ≧8,000 mPa·s, or ≧10,000 mPa·s, or ≧12,000 mPa·s, or ≧14,000 mPa·s.

[0058] D] The ethylene / alpha-olefin multi-block interpolymer (component a) has a viscosity of ≥ 0.860 g / cc, ≥ 0.862 g / cc, or ≥ 0.864 g / cc, or ≥ 0.866 g / cc, or ≥ 0.868 g / cc, or ≥ 0.870 g / cc, or ≥ 0.872 g / cc (1 cc = 1 cm 3 The composition according to any one of A] to C] above, having a density of (A] to C]).

[0059] E] A composition described in any one of A] to D] above, wherein component a has a density of ≦0.890 g / cc, or ≦0.888 g / cc, or ≦0.886 g / cc, or ≦0.884 g / cc, or ≦0.882 g / cc, or ≦0.880 g / cc, or ≦0.878 g / cc.

[0060] F] The composition described in any one of A] to E] above, wherein the ethylene / alpha-olefin multi-block interpolymer (component a) has a melt index (I2) of ≥ 100, or ≥ 200, or ≥ 300, or ≥ 400, or ≥ 500 dg / min.

[0061] G] A composition described in any one of A] to F] above, wherein component a has a melt index (I2) of ≦5,000, or ≦4,000, or ≦3,000, or ≦2,000, or ≦1,000 dg / min.

[0062] H] The ethylene / alpha-olefin multi-block interpolymer (component a) has a hard segment (HS) amount of ≥ 8 wt%, or ≥ 10 wt%, or ≥ 12 wt%, or ≥ 16 wt%, or ≥ 18 wt%, or ≥ 20 wt%, based on the weight sum of SS (soft segment) and HS. Composition according to any one of A] to G] above.

[0063] I] A composition described in any one of A] to H] above, in which component a has an HS amount of ≦40 wt%, or ≦35 wt%, or ≦30 wt%, or ≦28 wt%, or ≦26 wt%, or ≦24 wt%, based on the weight sum of SS and HS.

[0064] J] The ethylene / alpha-olefin multi-block interpolymer (component a) has an alpha-olefin content in the SS of ≧10 mol%, or ≧12 mol%, or ≧14 mol%, or ≧16 mol%, or ≧18 mol%, based on the total moles of monomers in the SS. The composition according to any one of A] to I] above.

[0065] K] The composition according to any one of A] to J] above, wherein component a has an alpha-olefin content in the soft segment (SS) of ≦40 mol%, or ≦35 mol%, or ≦30 mol%, or ≦28 mol%, or ≦26 mol%, or ≦24 mol%, or ≦22 mol%, or ≦20 mol%, based on the total moles of monomers in (SS).

[0066] L] The composition according to any one of the above [A] to [K], wherein the alpha-olefin of the ethylene / alpha-olefin multi-block interpolymer (component a) is a C3 to C20 alpha-olefin, and further a C3 to C10 alpha-olefin.

[0067] M] The composition according to any one of A] to L] above, wherein the alpha-olefin of component a is selected from propylene, 1-butene, 1-pentene, 1-hexene or 1-octene, further propylene, 1-butene or 1-octene, further propylene or 1-octene, and further 1-octene.

[0068] N] The composition according to any one of A] to M] above, wherein the ethylene / alpha-olefin multi-block interpolymer (component a) is an ethylene / alpha-olefin multi-block copolymer.

[0069] O] The composition according to any one of A] to N] above, wherein the ethylene / alpha-olefin multiblock interpolymer (component a) is selected from the following: ethylene / propylene multiblock copolymer, ethylene / butene multiblock copolymer, or ethylene / octene multiblock copolymer, further ethylene / butene multiblock copolymer, or ethylene / octene multiblock copolymer, and further ethylene / octene multiblock copolymer.

[0070] P] A composition according to any one of A] to O] above, wherein the anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer (component b) has a melt viscosity (190°C) of ≦45,000 mPa·s, or ≦40,000 mPa·s, or ≦35,000 mPa·s, or ≦30,000 mPa·s, or ≦28,000 mPa·s, or ≦26,000 mPa·s, or ≦24,000 mPa·s, or ≦22,000 mPa·s, or ≦20,000 mPa·s, or ≦18,000 mPa·s, or ≦16,000 mPa·s.

[0071] Q] A composition described in any one of A] to P] above, wherein component b has a melt viscosity (190°C) of ≧1,000 mPa·s, or ≧2,000 mPa·s, or ≧3,000 mPa·s, or ≧4,000 mPa·s, or ≧≧6,000 mPa·s, or ≧8,000 mPa·s, or ≧10,000 mPa·s, or ≧12,000 mPa·s, or ≧14,000 mPa·s.

[0072] R] A composition described in any one of A] to Q] above, wherein the anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer (component b) has a density of ≧0.888 g / cc, or ≧0.890 g / cc, or ≧0.892 g / cc, or ≧0.894 g / cc, or ≧0.896 g / cc, or ≧0.898 g / cc, or ≧0.900 g / cc, or ≧0.902 g / cc.

[0073] S] A composition described in any one of A] to R] above, wherein component b has a density of ≦0.920 g / cc, or ≦0.918 g / cc, or ≦0.916 g / cc, or ≦0.914 g / cc, or ≦0.912 g / cc, or ≦0.910 g / cc, or ≦0.908 g / cc, or ≦0.906 g / cc.

[0074] T] A composition described in any one of the above A] to S], wherein the anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer (component b) has a melting point (Tm) of ≧100°C, or ≧105°C, or ≧110°C, or ≧115°C, or ≧120°C, or ≧122°C, or ≧124°C, or ≧126°C, or ≧128°C, or ≧130°C, or ≧131°C.

[0075] The composition according to any one of the above [A] to [T], wherein component b has a melting point (Tm) of ≦160°C, or ≦155°C, or ≦150°C, or ≦148°C, or ≦146°C, or ≦144°C, or ≦142°C, or ≦140°C, or ≦138°C, or ≦136°C.

[0076] V] A composition according to any one of A] to U] above, wherein the anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer (component b) has a weight average molecular weight Mw of ≧10,000 g / mol, or ≧15,000 g / mol, or ≧20,000 g / mol, or ≧25,000 g / mol, or ≧30,000 g / mol, or ≧32,000 g / mol, or ≧34,000 g / mol, or ≧35,000 g / mol.

[0077] W] A composition according to any one of A] to V] above, wherein component b has a weight average molecular weight Mw of ≦60,000 g / mol or ≦55,000 g / mol, or ≦50,000 g / mol, or ≦48,000 g / mol, or ≦46,000 g / mol, or ≦44,000 g / mol, or ≦42,000 g / mol, or ≦40,000 g / mol.

[0078] X] A composition according to any one of A] to W] above, wherein the anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer (component b) has a number average molecular weight Mn of ≧6,000 g / mol, or ≧8,000 g / mol, or ≧10,000 g / mol, or ≧12,000 g / mol.

[0079] Y] A composition described in any one of A] to X] above, wherein component b has a number average molecular weight Mn of ≦40,000 g / mol, or ≦30,000 g / mol, or ≦28,000 g / mol, or ≦26,000 g / mol, or ≦24,000 g / mol, or ≦22,000 g / mol, or ≦20,000 g / mol, or ≦18,000 g / mol.

[0080] Z] A composition described in any one of A] to Y] above, wherein the anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer (component b) has a molecular weight distribution (Mw / Mn) of ≧2.00, or ≧2.10, or ≧2.20, or ≧2.30, or ≧2.40 g / mol.

[0081] A2] The composition according to any one of A] to Z] above, wherein component b has a molecular weight distribution (Mw / Mn) of ≦3.00, or ≦2.90, or ≦2.80, or ≦2.70, or ≦2.60, or ≦2.50.

[0082] B2] The composition according to any one of A] to A2] above, wherein the anhydride- and / or carboxylic acid-functionalized propylene-based polymer (component b) comprises ≧0.5 wt.%, or ≧0.6 wt.%, or ≧0.7 wt.%, or ≧0.8 wt.%, or ≧0.9 wt.%, or ≧1.0 wt.% of anhydride and / or carboxylic acid groups, based on the weight of the functionalized propylene-based polymer, and further wherein the anhydride and / or carboxylic acid groups are derived from maleic anhydride.

[0083] C2] The composition according to any one of A] to B2] above, wherein component b comprises ≦4.0 wt.%, or ≦3.5 wt.%, or ≦3.0 wt.%, or ≦2.5 wt.%, or ≦2.0 wt.%, or ≦1.8 wt.%, or ≦1.6 wt.%, or ≦1.4 wt.% of anhydride groups and / or carboxylic acid groups, based on the weight of the functionalized propylene-based polymer, and further wherein the anhydride groups and / or carboxylic acid groups are derived from maleic anhydride.

[0084] D2] The composition according to any one of A] to C2] above, wherein component b is an anhydride-functionalized and / or carboxylic acid-functionalized propylene / ethylene interpolymer, further an anhydride-functionalized and / or carboxylic acid-functionalized propylene / ethylene copolymer.

[0085] E2] A composition according to any one of A] to C2] above, wherein component b is an anhydride-functionalized and / or carboxylic acid-functionalized propylene / alpha-olefin interpolymer, and further anhydride-functionalized and / or carboxylic acid-functionalized propylene / alpha-olefin copolymer.

[0086] F2] The composition according to E2] above, wherein the alpha-olefin is a C4 to C20 alpha-olefin, further a C4 to C10 alpha-olefin, further selected from 1-butene, 1-pentene, 1-hexene or 1-octene, further 1-butene, 1-hexene or 1-octene, further 1-butene or 1-octene, further 1-octene.

[0087] G2] The composition according to any one of A] to F2] above, wherein component b is a grafted anhydride and / or propylene carboxylate-based polymer.

[0088] H2] The composition according to D2] above, wherein component b is a grafted anhydride and / or propylene carboxylate / ethylene interpolymer, and further a grafted anhydride and / or propylene carboxylate / ethylene copolymer.

[0089] I2] The composition according to E2] above, wherein component b is a grafted anhydride and / or propylene carboxylate / alpha-olefin interpolymer, and further a grafted anhydride and / or propylene carboxylate / alpha-olefin copolymer.

[0090] J2] The composition according to any one of the above I2], wherein the alpha-olefin is a C4 to C20 alpha-olefin, further a C4 to C10 alpha-olefin, further selected from 1-butene, 1-pentene, 1-hexene or 1-octene, further 1-butene, 1-hexene or 1-octene, further 1-butene or 1-octene, and further 1-octene.

[0091] K2] The composition according to any one of A] to J2] above, wherein the weight ratio of component a to component b is ≧0.10, or ≧0.15, or ≧0.20, or ≧0.22, or ≧0.24, or ≧0.26, or ≧0.28, or ≧0.30, or ≧0.32.

[0092] L2] A composition described in any one of A] to K2] above, wherein the weight ratio of component a to component b is ≦5.00, or ≦4.50, or ≦4.00, or ≦3.80, or ≦3.60, or ≦3.40, or ≦3.20, or ≦3.00.

[0093] M2] The composition according to any one of A] to L2] above, wherein the tackifier (component c) has a melt viscosity (160°C) of ≦1,200 mPa·s, or ≦1,100 mPa·s, or ≦1,000 mPa·s, or ≦900 mPa·s, or ≦850 mPa·s.

[0094] N2] The composition according to any one of A] to M2] above, wherein the tackifier (component c) has a melt viscosity (160°C) of ≥ 500 mPa·s, or ≥ 550 mPa·s, or ≥ 600 mPa·s, or ≥ 650 mPa·s, or ≥ 700 mPa·s, or ≥ 750 mPa·s.

[0095] O2] A composition described in any one of A] to N2] above, wherein the weight ratio of component c to component a is ≧1.00, or ≧1.05, or ≧1.10, or ≧1.15, or ≧1.20, or ≧1.25, or ≧1.30.

[0096] P2] A composition described in any one of A] to O2] above, wherein the weight ratio of component c to component a is ≦5.00, or ≦4.80, or ≦4.60, or ≦4.40, or ≦4.20, or ≦4.00.

[0097] Q2] A composition described in any one of A] to P2] above, wherein the weight ratio of component c to component b is ≧1.00, or ≧1.05, or ≧1.10, or ≧1.15, or ≧1.20, or ≧1.25, or ≧1.30.

[0098] R2] A composition described in any one of A] to Q2] above, wherein the weight ratio of component c to component b is ≦5.00, or ≦4.80, or ≦4.60, or ≦4.40, or ≦4.20, or ≦4.00.

[0099] S2] The composition according to any one of the above A] to R2], wherein component c is a hydrocarbon resin, further a hydrogenated hydrocarbon resin, further a hydrogenated alicyclic hydrocarbon resin.

[0100] T2] A composition described in any one of A] to S2] above, wherein the wax (component d) has a density of ≧0.920g / cc, or ≧0.925g / cc, or ≧0.930g / cc, or ≧0.932g / cc, or ≧0.934g / cc, or ≧0.936g / cc, or ≧0.938g / cc, or ≧0.939g / cc, or ≧0.940g / cc.

[0101] U2] A composition described in any one of A] to T2] above, wherein component d has a density of ≦0.960 g / cc, or ≦0.958 g / cc, or ≦0.956 g / cc, or ≦0.954 g / cc, or ≦0.952 g / cc, or ≦0.950 g / cc.

[0102] V2] A composition described in any one of A] to U2] above, wherein the wax (component d) has a melt viscosity (135°C) of ≧4.0 mPa·s, or ≧4.5 mPa·s, or ≧5.0 mPa·s, or ≧5.5 mPa·s, or ≧6.0 mPa·s.

[0103] W2] A composition described in any one of A] to V2] above, wherein component d has a melt viscosity (135°C) of ≦30 mPa·s, or ≦25 mPa·s, or ≦20 mPa·s, or ≦18 mPa·s, or ≦16 mPa·s, or ≦14 mPa·s, or ≦12 mPa·s, or ≦10 mPa·s.

[0104] X2] The composition according to any one of A] to W2] above, wherein the weight ratio of component d to component a is ≧0.40, or ≧0.45, or ≧0.50, or ≧0.55, or ≧0.60, or ≧0.62, or ≧0.64.

[0105] Y2] A composition described in any one of A] to X2] above, wherein the weight ratio of component d to component a is ≦4.00, or ≦3.50, or ≦3.00, or ≦2.80, or ≦2.60, or ≦2.40, or ≦2.20.

[0106] Z2] The composition according to any one of A] to Y2] above, wherein the weight ratio of component d to component b is ≧0.40, or ≧0.45, or ≧0.50, or ≧0.55, or ≧0.60, or ≧0.62, or ≧0.64.

[0107] A3] The composition according to any one of A] to Z2] above, wherein the weight ratio of component d to component b is ≦4.00, or ≦3.50, or ≦3.00, or ≦2.80, or ≦2.60, or ≦2.40, or ≦2.20.

[0108] B3] The composition according to any one of A] to A3] above, wherein component d is a Fischer-Tropsch wax.

[0109] C3] A composition according to any one of A] to B3] above, wherein the composition comprises ≧4.0 wt.%, or ≧6.0 wt.%, or ≧8.0 wt.%, or ≧10 wt.% of component a, based on the weight of the composition.

[0110] D3] A composition according to any one of A] to C3] above, comprising, based on the weight of the composition, ≦50 wt.%, or ≦45 wt.%, or ≦40 wt.%, or ≦38 wt.%, or ≦36 wt.%, or ≦34 wt.%, or ≦32 wt.%, or ≦30 wt.% of component a.

[0111] E3] A composition described in any one of A] to D3] above, wherein the composition contains ≧4.0 wt.%, or ≧6.0 wt.%, or ≧8.0 wt.%, or ≧10 wt.% of component b, based on the weight of the composition.

[0112] F3] A composition according to any one of A] to E3] above, wherein the composition comprises ≦50 wt.%, or ≦45 wt.%, or ≦40 wt.%, or ≦38 wt.%, or ≦36 wt.%, or ≦34 wt.%, or ≦32 wt.%, or ≦30 wt.% of component b, based on the weight of the composition.

[0113] G3] A composition described in any one of A] to F3] above, wherein the composition comprises ≧25 wt.%, or ≧30 wt.%, or ≧32 wt.%, or ≧34 wt.%, or ≧36 wt.%, or ≧38 wt.% of component c, based on the weight of the composition.

[0114] H3] A composition described in any one of A] to G3] above, wherein the composition comprises ≦60 wt.%, or ≦55 wt.%, or ≦50 wt.%, or ≦48 wt.%, or ≦46 wt.%, or ≦44 wt.%, or ≦42 wt.%, or ≦40 wt.% of component c, based on the weight of the composition.

[0115] I3] A composition described in any one of A] to H3] above, wherein the composition comprises ≧5.0 wt.%, or ≧10 wt.%, or ≧12 wt.%, or ≧14 wt.%, or ≧16 wt.%, or ≧18 wt.%, or ≧20 wt.% of component d, based on the weight of the composition.

[0116] J3] A composition according to any one of A] to I3] above, wherein the composition comprises ≦50 wt.%, or ≦45 wt.%, or ≦40 wt.%, or ≦35 wt.%, or ≦30 wt.%, or ≦28 wt.%, or ≦26 wt.%, or ≦24 wt.%, or ≦22 wt.% of component d, based on the weight of the composition.

[0117] K3] A composition according to any one of A] to J3] above, wherein the composition comprises ≧30.0 wt.%, or ≧32.0 wt.%, or ≧34.0 wt.%, or ≧36.0 wt.%, or ≧38.0 wt.% of the sum of components a and b, based on the weight of the composition.

[0118] L3] A composition described in any one of A] to K3] above, wherein the composition comprises, based on the weight of the composition, ≦50.0 wt.%, or ≦48.0 wt.%, or ≦46.0 wt.%, or ≦44.0 wt.%, or ≦42.0 wt.% of the sum of components a and b.

[0119] M3] A composition described in any one of A] to L3] above, wherein the composition comprises ≧50.0 wt%, or ≧60.0 wt%, or ≧70.0 wt%, or ≧80.0 wt%, or ≧90.0 wt%, or ≧92.0 wt%, or ≧94.0 wt%, or ≧96.0 wt%, or ≧98.0 wt%, or ≧99.0 wt%, of the sum of components a, b, c, and d, based on the weight of the composition.

[0120] N3] A composition described in any one of A] to M3] above, wherein the composition comprises ≦100.0% by weight, or ≦99.9% by weight, or ≦99.8% by weight, or ≦99.7% by weight, or ≦99.6% by weight, or ≦99.5% by weight of the sum of components a, b, c, and d, based on the weight of the composition.

[0121] O3] A composition described in any one of A] to N3] above, wherein the composition has a melt viscosity (177°C) of ≦8,000 mPa·s, or ≦7,000 mPa·s, or ≦6,000 mPa·s, or ≦5,000 mPa·s, or ≦4,000 mPa·s, or ≦3,000 mPa·s, or ≦2,000 mPa·s.

[0122] P3] The composition according to any one of A] to O3] above, wherein the composition has a melt viscosity (177°C) of ≥ 200 mPa·s, or ≥ 300 mPa·s, or ≥ 400 mPa·s, or ≥ 500 mPa·s, or ≥ 600 mPa·s, or ≥ 700 mPa·s, or ≥ 800 mPa·s, or ≥ 900 mPa·s, or ≥ 1,000 mPa·s, or ≥ 1,100 mPa·s, or ≥ 1,200 mPa·s, or ≥ 1,300 mPa·s.

[0123] Q3] The composition according to any one of A] to P3] above, wherein the composition has an open time of ≦30 seconds, or ≦28 seconds, or ≦26 seconds, or ≦24 seconds, the open time being as described herein.

[0124] R3) A composition according to any one of A] to Q3] above, wherein the composition has an open time of ≧10 seconds, or ≧12 seconds, or ≧14 seconds, or ≧16 seconds, or ≧18 seconds.

[0125] S3] The composition of any one of A]-R3] above, wherein the composition has a cure time of ≦2.0 seconds, or ≦1.5 seconds, or ≦1.0 seconds, wherein the cure time is as described herein.

[0126] T3] The composition according to any one of [A]-[S3] above, wherein the composition has a fiber tear (at 70° C.) of ≧90%, or ≧91%, or ≧92%, or ≧93%, or ≧94%. Fiber tear is as described herein.

[0127] U3] A composition described in any one of [A] to [T3] above, wherein the composition has a fiber tear (at -20°C) of ≧90%, or ≧92%, or ≧94%, or ≧96%, or ≧98%, or ≧99%.

[0128] V3] The composition according to any one of [A] to [U3] above, wherein the composition has a fiber tear of ≧90%, or ≧91%, or ≧92%, or ≧93%, or ≧94% at a temperature of -20°C to 70°C.

[0129] W3] The composition of any one of A]-V3] above, wherein the composition has a PAFT of ≥ 70°C, or ≥ 71°C, or ≥ 72°C, or ≥ 73°C, or ≥ 74°C, or ≥ 75°C. The PAFT is described herein.

[0130] X3] The composition of any one of A]-W3] above, wherein the composition has a SAFT of ≥100° C., or ≥101° C., or ≥102° C., or ≥103° C., or ≥104° C., or ≥105° C., or ≥106° C. The SAFT is as described herein.

[0131] Y3] The composition described in any one of A] to X3] above, further comprising at least one additive, and at least one antioxidant.

[0132] Z3] The composition described in any one of A] to Y3] above, further comprising a thermoplastic polymer different from the ethylene / alpha-olefin multi-block interpolymer (component a) in one or more characteristics, such as monomer(s) type, distribution, and / or amount, melt viscosity (177°C), density, melt index (I2), or any combination thereof.

[0133] A4] The composition according to any one of the above A] to Z3], which is an adhesive composition, and further is a hot melt adhesive or a pressure sensitive adhesive, and further is a hot melt adhesive.

[0134] B4] An article comprising at least one component formed from the composition described in any one of A] to A4] above.

[0135] C4] The article of B4] above, wherein the composition bonds two surfaces of the article together.

[0136] D4] An article according to B4] or C4] above, wherein the article is a package or container.

[0137] Test Method Melt Viscosity Melt viscosities were measured according to ASTM D 3236 using a Brookfield Viscometer (Model DV0III, Version 3) and an SC-31 hot melt viscometer spindle at the following temperatures: a) 177°C for the ethylene / alpha-olefin multi-block interpolymers, b) 177°C for the compositions, and c) 190°C for the functionalized propylene-based polymers. This method can also be used to measure the melt viscosities of waxes (at 135°C) and tackifiers (at 160°C). The samples were poured into aluminum disposable tube-shaped chambers, which were inserted into a Brookfield Thermosel and secured in place. The sample chamber had a notch at the bottom that matched the bottom of the Brookfield Thermosel to prevent the chamber from rotating when the spindle was inserted and rotated. The sample (approximately 8-10 grams) was heated to the required temperature until the molten sample was 1 inch below the top of the sample chamber. The viscometer apparatus was lowered and the spindle was submerged in the center of the sample chamber. The spindle was not allowed to touch the sides of the chamber. The descent continued until the bracket on the viscometer was aligned on the Thermosel. The viscometer was turned on and set to run at a steady shear rate that gave a torque reading within the range of 40-60 percent of the full torque capacity, based on the rpm output of the viscometer. Readings were taken every 15 minutes or until the value stabilized, at which point the final reading was recorded.

[0138] Fiber tearing The fiber tear (%) of each adhesive composition was measured according to a standardized method using Inland corrugated board. The composition was heated to 177°C, then a bead of the composition was applied (at a weight of 2.1 grams per meter) onto a corrugated board coupon (25.4 mm x 76.2 mm) by drawing the sample composition down the length of the cardboard coupon with a spatula or hot melt applicator. A second coupon was quickly (within 1 second) placed on top of the applied composition for 10 seconds with a pressure of 2.5 bar (250 kPa) to hold the bond in place. The test samples were conditioned for 24 hours at 23°C (room temperature) and then at least 24 hours at each test temperature (-20°C, 0°C, 23°C, and 70°C). Immediately after conditioning, the samples (n=5) were peeled apart by inserting a spatula blade under one corner and folding the corner of the cardboard. The sample was then placed on a horizontal surface with the side having the folded corner facing up. The folded corner was manually pulled as quickly as possible at an angle of approximately 45° to 90° relative to the longitudinal axis of the coupon to tear the adhesive bond. If applicable, the test sample was held as close as possible to a heating or cooling source, each set to the respective test temperature, during this manual pulling. The percentage of torn fibers remaining on the surface of the adhesive composition (fiber tear) was evaluated in 25% increments (i.e., 0%, 25%, 50%, 75%, and 100%) and the average value of the five test samples was recorded.

[0139] Peel Adhesion Failure Temperature (PAFT) and Shear Adhesion Failure Temperature (SAFT) Peel Adhesion Failure Temperature (PAFT) was tested according to ASTM D4498 using a Cheminstruments OSI-8 programmable oven with a 100 gram weight. Each test specimen was first equilibrated in the oven at 40° C. for 10 minutes, and the oven temperature was increased at an average rate of 0.5° C. / min. The temperature at which the adhesive bond failed was recorded. Each test specimen was in a peel mode configuration with a 100 gram weight.

[0140] The shear adhesive failure temperature (SAFT) was measured according to ASTM D4498 using a Cheminstruments OSI-8 programmable oven with a 500 gram weight. Each test specimen was first equilibrated in the oven at 40° C. for 10 minutes, and the oven temperature was increased at an average rate of 0.5° C. / min. The temperature at which the adhesive bond failed was recorded. Each test specimen was in a shear mode configuration with a 500 gram weight.

[0141] Each test specimen for the PAFT or SAFT test was prepared by subjecting each test specimen to a 60 g / m 2 A 1.75" or 2" (45 mm or 51 mm) wide strip of a single-sided pressure-sensitive tape such as masking tape was adhered parallel to the bottom sheet lengthwise, separated by a 1" (25 mm) gap. The two strips of tape were positioned so that the 1" gap ran lengthwise down the center of the bottom sheet.

[0142] The adhesive composition to be tested was heated to 177°C (350°F) and then evenly dispensed into the center of the "1 inch gap" formed between the two strips of tape. A bonded paper template was then quickly formed before the composition could thicken too much, as follows: A rod was quickly slid onto the bottom sheet to flatten the adhesive composition in the gap. The rod was shimmed with the same strips of tape on both sides of the gap. After the first rod had passed, a second sheet of Kraft paper was aligned with the bottom sheet and placed on top of it, and a second rod was quickly slid onto the top sheet to form the bonded paper template. Overall, the first rod evenly spread the composition in the gap between the tape strips, and the second rod evenly compressed the second sheet covering the top of the gap and the top of the tape strip. Within the bonded paper template, a single 1 inch (25.4 mm) wide strip of adhesive composition bonded the bottom and top paper sheets. The paper template was cut crosswise into 1 inch (25.4 mm) wide and 3 inch (76.2 mm) long strips to form the test specimens. Each test specimen had a central 1 inch by 1 inch adhesive bond area. Each test specimen was conditioned for 24 hours at room temperature (23° C.) and 54% relative humidity. The test specimens were then used in the PAFT and SAFT tests as described above. In each test, two test specimens from each composition were tested and the average failure temperature was recorded.

[0143] Open and cure times Cure and open times were measured using an INATEC Bond Tester, a mechanical testing device used to form and tear test bonds. The INATEC Bond Tester was heated to 173°C, and this temperature was measured by a handheld thermocouple. The bottom substrate, 2.5 in. (63.5 mm) x 2 in. (50.8 mm) cardboard, moved on a track under the adhesive pot, delivering a bead of adhesive in the range of 0.26 to 0.29 g / linear m. The adhesive pot pressure was increased or decreased as necessary to maintain a constant bead size. A top substrate of 2.5 in. (63.5 mm) x 2 in. (50.8 mm) cardboard was applied over the bottom substrate with a pressure of 2.5 bar (250 kPa). The INATEC had two timers that could measure the cure and open times in seconds.

[0144] Set Time Measurement Set time is the shortest compression time required to achieve at least 50% fiber tear. In this test, the release time was set at 2 seconds (sec). The top substrate was compressed onto the bottom substrate to form a bond. After a preset compression time of 5 seconds, a tear test was performed while pulling the top substrate away from the bottom substrate. A visual evaluation was then performed to determine the percentage of fiber tear achieved under the preset test conditions. Based on this result, the compression time was increased or decreased in 1 second intervals to determine compression times that achieved 50% or more fiber tear and compression times that achieved less than 50% fiber tear. Set time was recorded as the shortest compression time that resulted in a minimum of 50% fiber tear.

[0145] Measurement of Open Time The open time is the longest test time from application of the adhesive to one substrate to bonding with a second substrate, where the bond results in at least 50% fiber tear. For the test, the compression time was set to 15 seconds. For the measurement of the open time, the test time was preset to 10 seconds and increased in 10 second intervals until less than 50% fiber tear was achieved. The test time at which the fiber tear % began to drop below 50% was recorded, and then the test time was reduced by 5 seconds and the fiber tear % was determined. The test time required for the fiber tear % to begin to drop below 50% was recorded. Finally, relative to this second recorded time, the test time was reduced by 1 second to determine the maximum test time to achieve 50% or more fiber tear.

[0146] Fourier Transform Infrared Spectroscopy (FTIR)-Determination of Maleic Anhydride Content (MAH) in Functionalized Propylene-Based Polymers The concentration of maleic anhydride is 1791 cm -1 The peak height is determined by the ratio of the maleic anhydride peak height to the polymer reference peak at wavenumber 1156 cm in the case of polyethylene. -1 The maleic anhydride content is calculated by multiplying this ratio by the appropriate calibration constant. (The equation used for maleic acid grafted olefin-based polymers using the polypropylene reference peak has the following form, as shown in Equation A1.

[0147] MAH(weight%)=A*{[1791cm -1 FTIR peak area at 1156cm -1 FTIR peak area at 1712cm -1 FTIR peak area at 1156cm -1 FTIR peak area at 1000 nm} (Equation A1)

[0148] The calibration constant A can be determined using a 13C NMR standard. The actual calibration constant may vary slightly depending on the instrument and polymer. Wavenumber 1712 cm -1 The second component, , is the main source of maleic acid, which is negligible for freshly grafted material. However, over time, maleic anhydride can be readily converted to maleic acid in the presence of moisture. Depending on the surface area, significant hydrolysis can occur in just a few days under ambient conditions. The acid is expressed at a wavenumber of 1712 cm -1 The constant B in Equation A1 was a correction for the difference in extinction coefficients between the anhydride and acid groups.

[0149] Samples were prepared by pressing the functionalized polymer to a thickness of about 0.05-0.15 millimeters between two protective films at 150-180 °C in a heated press for 1 hour. MYLAR and TEFLON were the preferred protective films to protect the samples from the platens. Aluminum foil should never be used because maleic anhydride reacts with aluminum. The platens should be pressed (about 10 tons) for about 5 minutes. The samples are cooled to room temperature and placed in a suitable sample holder before scanning with the FTIR. A background scan should be performed before each sample scan or as needed. The accuracy of the test was good, with an inherent variability of less than ±5%. Samples should be stored with a desiccant to prevent excessive hydrolysis. The moisture content in the product was measured to as low as 0.1 weight percent. However, the conversion of the anhydride to the acid is reversible with temperature, and complete conversion can take up to a week. Recovery is best done in a vacuum oven at 150°C and requires sufficient vacuum (>27 inches Hg). If the vacuum is insufficient, the sample will tend to oxidize and reach a temperature of approximately 1740 cm. -1 The infrared peaks at about 1791 cm and 1803 cm give values ​​that are too low for the grafting level. Maleic anhydride and acid have infrared peaks at about 1791 cm and 1803 cm, respectively. -1 and 1712 cm -1 The peak was represented by.

[0150] Differential Scanning Calorimetry (DSC) Differential scanning calorimetry (DSC) was used to measure the Tm, Tc, Tg, and crystallinity of the propylene-based (PP) and ethylene-based (PE) samples. The samples (0.5 g) were each compression molded into a film at 25000 psi for 10-15 seconds at 190°C. Approximately 5-8 mg of film sample was weighed and placed in the DSC pan. A lid was crimped onto the pan to ensure a closed atmosphere. The sample pan was placed in the DSC cell and then heated at a rate of approximately 10°C / min to a temperature of 230°C for PP (180°C for PE). The samples were held at this temperature for 3 minutes. The samples were then cooled at a rate of 10°C / min to -60°C for PP (-90°C for PE) and held isothermal at that temperature for 3 minutes. The samples were then heated at a rate of 10°C / min until completely melted (second heat). Unless otherwise stated, the melting point (Tm) and glass transition temperature (Tg) of each polymer sample were determined from the second heat curve, and the crystallization temperature (Tc) was determined from the first cooling curve. Tg and the respective peak temperatures of Tm and Tc were recorded. Percent crystallinity can be calculated by dividing the heat of fusion (Hf) determined from the second heat curve by the theoretical heat of fusion of 165 J / g for PP (292 J / g for PE) and multiplying this amount by 100 (e.g., % crystallinity = (Hf / 165 J / g) x 100 for PP).

[0151] Polymer Density Polymer density was measured according to ASTM D-792.

[0152] Gel Permeation Chromatography - Ethylene-Based Polymers The chromatography system consisted of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven compartment was set at 160° C. and the column compartment was set at 150° C. The columns were four AGILENT "Mixed A" 30 cm, 20 micron linear mixed bed columns. The chromatography solvent was 1,2,4-trichlorobenzene containing 200 ppm butylated hydroxytoluene (BHT). The solvent source was sparged with nitrogen. The injection volume was 200 microliters and the flow rate was 1.0 milliliters / min.

[0153] Calibration of the GPC column set is performed with 21 narrow molecular weight distribution polystyrene standards with molecular weights ranging from 580 to 8,400,000 g / mol, prepared as six "cocktail" mixtures with at least 10-fold separation between individual molecular weights. Standards are purchased from Agilent Technologies. Polystyrene standards are prepared in 0.025 grams in 50 milliliters of solvent for molecular weights of 1,000,000 or greater, and 0.05 grams in 50 milliliters for molecular weights less than 1,000,000. The polystyrene standards are dissolved at 80° C. with gentle agitation for 30 minutes. The polystyrene standard peak molecular weights are converted to polyethylene molecular weights using Equation 1 (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)).

[0154] M ポリエチレン =A×(M ポリスチレン ) B (Formula 1) where M is the molecular weight, A has a value of 0.4315, and B is equal to 1.0.

[0155] A fifth order polynomial is used to fit each of the polyethylene equivalent calibration points. A small adjustment (approximately 0.375 to 0.445) is made to A to correct for column resolution and band broadening effects such that the linear homopolymer polyethylene standard is obtained at 120,000 Mw.

[0156] Total plate counts for the GPC column set are performed using decane (prepared at 0.04 g in 50 milliliters of TCB and dissolved for 20 minutes with gentle agitation). Plate counts (Equation 2) and symmetry (Equation 3) are measured with a 200 microliter injection according to the following equation:

[0157]

number

[0158]

number

[0159] Samples are prepared semi-automatically using the PolymerChar "Instrument Control" software to target sample weight at 2 mg / mL and add solvent (containing 200 ppm BHT) via the PolymerChar high temperature autosampler to a septa-capped vial that has been pre-sparged with nitrogen. Samples are dissolved at 160° C. for 2 hours under "slow" shaking.

[0160] Mn (GPC) , Mw (GPC) , and Mz (GPC) is calculated based on GPC results using PolymerChar GPCOne™ software, the IR chromatograph with baseline subtraction at each equally spaced data collection point (i), and the polyethylene equivalent molecular weight obtained from a narrow standard calibration curve at point (i) from Equation 1, using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR chromatograph according to Equations 4-6. Equations 4-6 are as follows:

[0161]

number

[0162] To monitor deviations over time, a flow marker (decane) is introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow marker (FM) is used to linearly correct the pump flow rate (Flow (Apparent)) of each sample by aligning the RV of the respective decane peak in the sample (RV (FM Sample)) with that of the decane peak in the narrow standard calibration (RV (FM Calibrated)). Any change in time of the decane marker peak is then assumed to be related to a linear shift in flow rate (Flow (Effective)) throughout the run. To facilitate the highest accuracy of the RV measurement of the flow marker peak, a least-squares fitting routine is used that fits the peaks of the flow marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation is then used to solve for the true peak position. After calibrating the system based on the flow marker peak, the effective flow rate (with respect to the narrow standard calibration) is calculated as in Equation 7: Flow (Effective) = Flow (Apparent) * (RV (FM Calibrated) / RV (FM Sample)) (Equation 7). Processing of flow marker peaks is performed via PolymerChar GPCOne™ software. Acceptable flow corrections are those where the effective flow rate is within + / - 0.7% of the apparent flow rate.

[0163] Gel Permeation Chromatography (GPC) - Propylene-Based Polymers A high temperature gel permeation chromatography (GPC) system equipped with a Robotic Assistant Deliver (RAD) system for sample preparation and sample injection can be used. The concentration detector is an infrared detector (IR4) from Polymer Char Inc. (Valencia, Spain). Data collection is performed using a Polymer Char DM100 data acquisition box. The system is equipped with an online solvent degasser from AGILENT. The column compartment is operated at 150°C. The columns are four "Mixed A" LS 30 cm, 20 micron columns. The solvent is 1,2,4-trichloro-benzene (TCB) purged with nitrogen (N2) containing approximately "200 ppm" 2,6-di-t-butyl-4-methylphenol (BHT). The flow rate is 1.0 mL / min and the injection volume is 200 μL. A sample concentration of 2 mg / mL is prepared by dissolving the sample in N2-purged and preheated TCB (containing 200 ppm BHT) at 160° C. for 2.5 hours with gentle stirring.

[0164] The GPC column set is calibrated by running 20 narrow molecular weight distribution polystyrene (PS) standards. The molecular weights (MW) of the standards range from 580 to 8,400,000 g / mol, and the standards are contained in six "cocktail" mixtures. Each standard mixture has at least a 10-fold interval between the individual molecular weights. The equivalent polypropylene molecular weight of each PS standard is calculated using the Mark-Houwink coefficients reported for polypropylene (Th. G. Scholte, NL J Meijerink, HM Schoffeleers and AMG Brands, J. Appl. Polym. Sci., 29, 3763-3782 (1984)) and polystyrene (EP Tokka, RJ Roe, NY Hellman, PM Muglia, Macromolecules, 4, 507 (1971)) using the following equation (1):

[0165]

number

[0166] [Table 1]

[0167] Logarithmic molecular weight calibrations are generated using fourth order polynomial regression as a function of elution volume. Number average and weight average molecular weights are calculated according to the following formulas:

[0168]

number

[0169] 13C NMR to measure the amount of hard segments (HS) and the amount of alpha-olefins in the soft segments (SS) in ethylene / alpha-olefin multiblock interpolymers 13C NMR spectroscopy is one of several techniques known in the art for measuring the incorporation of comonomers into polymers. An example of this technique is described in Randall (Journal of Macromolecular Science, Reviews in Macromolecular Chemistry and Physics, C29(2&3), 201-317(1989)), incorporated herein by reference in its entirety, for measuring the comonomer content of ethylene / alpha-olefin copolymers. The basic procedure for determining the comonomer content of ethylene / alpha-olefin interpolymers involves acquiring a 13C NMR spectrum under conditions in which the intensity of the peaks corresponding to the different carbons in the sample is directly proportional to the total number of contributing nuclei in the sample. Methods to ensure this proportionality are known in the art and include allowing sufficient time for relaxation after the pulse, gated decoupling techniques, the use of relaxation agents, etc. The relative intensity of a peak or peaks is actually obtained by computer integration of the peaks. After acquiring the spectrum and integrating the peaks, those peaks associated with the comonomers are assigned. This assignment can be made by reference to known spectra or literature, or by synthesis and analysis of model compounds, or by the use of isotopically labeled comonomers. The mole % of comonomer can be determined by the ratio of the integral corresponding to the moles of comonomer to the integral corresponding to the moles of total monomer in the interpolymer, as described in the Randall reference cited above.

[0170] Since the hard segment (or hard segments) in the ethylene / alpha-olefin multiblock interpolymers generally have less than about 2.0 wt. % of comonomer, its main contribution to the spectrum is only for the integral at about 30 ppm. The hard segments contributing to the "not at 30 ppm" peak are assumed to be negligible at the beginning of the analysis. Therefore, for the starting point, the integral of the "not at 30 ppm" peak is assumed to come only from the soft segment (or soft segments). These integrals are fitted to a first-order Markov statistical model for the copolymer using linear least squares minimization to determine the fitting parameters used (i.e., the probability of octene insertion after octene P oo and the probability of octene insertion after ethylene P eo ) is generated and the contribution of the soft segment to the 30 ppm peak is calculated. The difference between the "total measured 30 ppm peak integral" and the "calculated contribution of the soft segment integral to the 30 ppm peak" is the contribution from the hard segment. Thus, the experimental spectrum is now deconvoluted into two integral lists describing the soft and hard segments, respectively. The calculation of the weight percent of the hard segment is not complicated and is calculated by the ratio of the integral sum over the hard segment spectrum to the integral sum over the entire spectrum.

[0171] From the deconvoluted soft segment integral list, the comonomer composition can be calculated, for example, according to the method of Randall. From the comonomer composition of the entire spectrum and the comonomer composition of the soft segment, a mass balance can be used to calculate the comonomer composition of the hard segment. From the comonomer composition of the hard segment, Bernoulli statistics are used to calculate the hard segment contribution to the integral of the "non-30 ppm peak". Since there is usually very little octene present in the hard segment, typically about 0 to about 1 mol%, Bernoulli statistics is a reasonable and robust approximation. These contributions are then subtracted from the experimental integral of the "non-30 ppm peak". The resulting "non-30 ppm peak" integral is then fitted to a first-order Markov statistical model for the copolymer, as described in the paragraph above. The iterative process is performed in the following manner: fit the total "non-30 ppm peaks", then calculate the soft segment contribution to the 30 ppm peaks, then calculate the soft / hard segment split, then calculate the hard segment contribution to the "non-30 ppm peaks", then correct the hard segment contribution to the "non-30 ppm peaks", and fit the resulting "non-30 ppm peaks". This is repeated until the values ​​for the soft / hard segment split converge to a minimum error function. The final comonomer composition for each segment is reported.

[0172] Validation of the measurements is achieved through the analysis of several in situ polymer blends. By design of polymerization and catalyst concentration, the expected splitting is compared to the measured NMR splitting values. Table B shows the chemical shift assignments for ethylene octene polymers.

[0173] [Table 2]

[0174] The following experimental procedure can be used: Each sample was prepared by adding approximately 2.6 grams of a 50 / 50 mixture of tetrachloroethane-d2 / orthodichlorobenzene, 0.025M in chromium acetylacetonate (relaxation agent), to a 0.2 gram sample of polymer in a 10 mm NMR tube. The sample is dissolved and homogenized by heating the tube and its contents to 150° C. Data is collected using a Bruker 400 MHz spectrometer equipped with a Bruker Dual DUL high temperature CryoProbe. Data is acquired at a sample temperature of 120° C. using 160 scans per data file, a pulse repetition delay of 6 seconds. Acquisition is performed using a spectral width of 25,000 Hz and a file size of 32K data points.

[0175] Melt Index The melt index (I2) of the ethylene-based polymers was measured according to ASTM D-1238, condition 190° C. / 2.16 kg. The melt flow rate (MFR) of the propylene-based polymers was measured according to ASTM D-1238, condition 230° C. / 2.16 kg.

[0176] experiment Commercially available polymers and additives The polymers, tackifiers, and other ingredients are listed in Table 1. The compositions are listed in Table 2.

[0177] [Table 3]

[0178] Synthesis of Ethylene / Alpha-Olefin Multiblock Copolymers Continuous solution polymerizations were carried out in a batch reactor (e.g., CSTR) equipped with an internal stirrer. Purified mixed alkane solvent (ISOPAR E available from ExxonMobil), monomer, and molecular weight regulator (hydrogen or chain shuttling agent) were fed to a 3.8 L reactor jacketed for temperature control. Solvent feed to the reactor was measured by a mass flow controller. A pump controlled the solvent flow rate and pressure to the reactor. At the discharge of the pump, a side stream was taken to provide flush flows to the injection lines for the procatalyst, cocatalyst, and chain shuttling agent (catalyst component solutions). These flows were measured and controlled to maintain an efficient production rate. The remaining solvent was mixed with the monomer and hydrogen and fed to the reactor. The temperature of the solvent / monomer solution was controlled by using a heat exchanger. This solution stream entered the bottom of the reactor.

[0179] The catalyst component solutions were metered using pumps and flow meters and combined with the catalyst flush solvent and introduced into the bottom of the reactor. The reactor was filled with liquid at 500 psig with vigorous stirring. Polymer was removed through an exit line at the top of the reactor. The reactor effluent was quenched by addition and reaction of a suitable reagent (water) and other additives were added for polymer stabilization. Following catalyst quenching and additive addition, the polymer was removed from the non-polymer stream by devolatilization. The isolated polymer melt was pelletized and collected. Process details are included in Table 2.

[0180] [Table 4] 1 .Standard cm 3 / min 2 .[N-(2,6-di(1-methylethyl)phenyl)amido)(2-isopropylphenyl)(α-naphthalene-2-diyl(6-pyridine-2-diyl)methane)]hafnium dimethyl 3.Bis-(1-(2-methylcyclohexyl)ethyl)2-oxoyl-3,5-di(t-butyl)phenyl)imino)zirconium dimethyl 4 .Diethylzinc 5 .Methyldi(C) of tetrakis(pentafluorophenyl)borate 14~18 Alkyl)ammonium salt mixture 6 Polymer formation rate 7 Ethylene conversion rate in the reactor 8 Efficiency, kg polymer / g M (where g M=g Hf+g Zr)

[0181] Preparation of Adhesive Composition For each composition, the corresponding ingredients shown in Table 3 were weighed into a steel container and preheated in an oven for 30 minutes at a temperature of 177° C. The mixture was then melt blended in a heating block using a "Paravisc style" mixhead operating at 100 revolutions per minute (rpm) at a temperature of 177° C. for 10 minutes. The viscosity and adhesive properties of the compositions are shown in Table 3.

[0182] [Table 5] CS=comparison sample * The values ​​in the table are weight percent (wt%) based on the total weight of the composition. † Viscosity of the composition ‡Percentage of fiber tear on cardboard box

[0183] As seen in Table 3, in comparison to the comparative compositions (CS.1, CS.2, and CS.3), the inventive compositions (Example 1, Example 2, and Example 3) exhibited the following properties: (i) higher percent fiber tear at 70° C., (ii) higher PAFT (>70° C.), and (iii) higher SAFT (>100° C.). The inventive compositions also had lower viscosity (177° C.) and excellent fiber tear at −20° C., 0° C., and 23° C., with 100% results for each test temperature. The inventive compositions also exhibited shorter cure times (≦1 second) than the comparative composition CS.3. The present invention includes the following aspects. Section 1. Ingredients include: a) an ethylene / alpha-olefin multi-block interpolymer having a melt viscosity (177°C) of ≦50,000 mPa·s; b) an anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer having a melt viscosity (190°C) of ≦50,000 mPa·s; c) a tackifier; and d) a wax. Section 2. Item 2. The composition according to item 1, wherein the ethylene / alpha-olefin multi-block interpolymer (component a) has a melt viscosity (177 ° C.) of ≥ 1,000 mPa · s. Section 3. Item 3. The composition according to item 1 or 2, wherein the ethylene / alpha-olefin multi-block interpolymer (component a) is an ethylene / alpha-olefin multi-block copolymer. Section 4. The composition according to any one of items 1 to 3, wherein the anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer (component b) has a melt viscosity (190°C) of ≥ 1,000 mPa·s. Section 5. The composition according to any one of items 1 to 4, wherein the ethylene / alpha-olefin multi-block interpolymer (component a) has a density of 0.860 g / cc to 0.890 g / cc. Section 6. The composition according to any one of items 1 to 5, wherein the anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer (component b) has a density of 0.888 g / cc to 0.920 g / cc. Section 7. Item 7. The composition according to any one of items 1 to 6, wherein the anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer (component b) has a melting point (Tm) of 100°C to 160°C. Section 8. 8. The composition according to any one of items 1 to 7, wherein component b is a grafted anhydride and / or propylene carboxylate-based polymer. Section 9. Item 9. The composition according to any one of items 1 to 8, wherein component b is an anhydride-functionalized and / or carboxylic acid-functionalized propylene / ethylene copolymer. Section 10. 10. The composition according to any one of items 1 to 9, wherein the weight ratio of component a to component b is 0.10 to 5.00. Section 11. 11. The composition according to any one of items 1 to 10, wherein the weight ratio of component c to component a is 1.00 to 5.00. Section 12. Item 12. The composition according to any one of items 1 to 11, wherein the weight ratio of component c to component b is 1.00 to 5.00. Section 13. Item 13. The composition according to any one of items 1 to 12, wherein component c is a hydrocarbon resin. Section 14. Item 14. The composition according to any one of items 1 to 13, wherein the wax (component d) has a density of 0.920 g / cc to 0.960 g / cc. Section 15. Item 15. The composition according to any one of items 1 to 14, wherein the wax (component d) has a melt viscosity (135°C) of 40 mPa·s to 30 mPa·s. Section 16. Item 16. The composition according to any one of items 1 to 15, wherein the composition contains 30.0% by weight to about 50.0% by weight of the sum of components a and b, based on the weight of the composition. Section 17. Item 17. The composition according to any one of items 1 to 16, wherein the composition has a melt viscosity (177°C) of 200 mPa·s to 8,000 mPa·s. Section 18. Item 18. The composition according to any one of items 1 to 17, wherein the composition has a cure time of ≦2.0 seconds. Section 19. Item 19. The composition according to any one of items 1 to 18, wherein the composition has a fiber tear (at 70° C.) of ≧90%. Section 20. An article comprising at least one component formed from the composition according to any one of claims 1 to 19.

Claims

1. Ingredients below: a) an ethylene / alpha-olefin multi-block interpolymer having a melt viscosity (177° C.) of ≦50,000 mPa·s; b) an anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer having a melt viscosity (190° C.) of ≦50,000 mPa·s; c) a tackifier; and d) a wax, the weight ratio of component a to component b is 0.10 to 5.00; the weight ratio of component c to component a is 1.00 to 5.00; the weight ratio of component c to component b is 1.00 to 5.00; the composition comprises 30.0% to 50.0% by weight of the sum of components a and b, based on the weight of the composition; the weight ratio of component d to component a is 0.40 to 4.00; A composition, wherein the weight ratio of component d to component b is from 0.40 to 4.

00.

2. 2. The composition of claim 1, wherein the ethylene / alpha-olefin multi-block interpolymer (component a) has a melt viscosity (177° C.) of ≧1,000 mPa·s.

3. The composition of claim 1 or 2, wherein the ethylene / alpha-olefin multi-block interpolymer (component a) is an ethylene / alpha-olefin multi-block copolymer.

4. The composition according to any one of claims 1 to 3, wherein the anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer (component b) has a melt viscosity (190°C) of ≥ 1,000 mPa·s.

5. The composition of any one of claims 1 to 4, wherein the ethylene / alpha-olefin multi-block interpolymer (component a) has a density from 0.860 g / cc to 0.890 g / cc.

6. The composition of any one of claims 1 to 5, wherein the anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer (component b) has a density of from 0.888 g / cc to 0.920 g / cc.

7. The composition according to any one of claims 1 to 6, wherein the anhydride-functionalized and / or carboxylic acid-functionalized propylene-based polymer (component b) has a melting point (Tm) of from 100°C to 160°C.

8. The composition according to any one of claims 1 to 7, wherein component b is a grafted propylene anhydride and / or carboxylate based polymer.

9. The composition according to any one of claims 1 to 8, wherein component b is an anhydride-functionalized and / or carboxylic acid-functionalized propylene / ethylene copolymer.

10. The composition according to any one of claims 1 to 9, wherein component c is a hydrocarbon resin.

11. A composition according to any one of the preceding claims, wherein the wax (component d) has a density of from 0.920 g / cc to 0.960 g / cc.

12. 12. The composition according to any one of the preceding claims, wherein the wax (component d) has a melt viscosity (135°C) of from 40 mPa·s to 30 mPa·s.

13. The composition according to any one of claims 1 to 12, wherein the composition has a melt viscosity (177°C) of from 200 mPa·s to 8,000 mPa·s.

14. The composition of any one of claims 1 to 13, wherein the composition has a cure time of ≦2.0 seconds.

15. The composition of any one of claims 1 to 14, wherein the composition has a fiber tear (at 70°C) of ≧90%.

16. An article comprising at least one component formed from the composition of any one of claims 1 to 15.

Citation Information

Patent Citations

  • Adhesive and marking composition made from ethylene / α-olefin copolymer

    JP2008545811A

  • Adhesive composition containing low molecular weight functionalized olefinic polymer

    JP2017531060A